Analysis of High-Fatality Accident on Toll Road and Its Countermeasures (Case Study: Tol Cipularang KM 91) - Robby Yudo Purnomo; Tri Tjahjono; Aswin Azhar Siregar (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2020)
Traffic accidents often occurred at toll roads in Indonesia. The free-flow speed and good road conditions indirectly encourage the driver to drive a vehicle at high speed. However, the driver's inability to control the vehicle at high speed can actually increase the probability of a traffic accident. One of the toll roads that are prone to accidents is the Cipularang Toll Road. At the end of 2019, there was a high-fatality crash at KM 91 of the toll road. Moreover, this road section is one of the black spots of the Cipularang Toll Road. Road geometric factors and vehicle conditions are the main factors for accidents. The high number of light and heavy vehicles also increases the chance of accidents given the difference in speed and size between the two types of vehicles. Some recommendations that can be implemented to reduce accidents include the application of incident management tools, installation of chevron markers, and construction of escape ramps. ABSTRAK Kecelakaan di jalan tol bukan hal yang baru di Indonesia. Faktor bebas hambatan dan kondisi jalan yang baik secara tidak langsung mendukung pengemudi untuk memacu kendaraan dengan kecepatan tinggi. Namun, ketidakmampuan pengemudi dalam mengendalikan kendaraan dalam kecepatan tinggi justru dapat meningkatkan probabilitas terjadinya kecelakaan. Salah satu jalan tol yang rawan kecelakaan adalah Ruas Tol Cipularang. Pada tahun akhir tahun 2019, telah terjadi kecelakaan menonjol pada KM 91 tol tersebut. Ruas jalan tersebut merupakan salah satu blackspot dari Tol Cipularang. Faktor geometrik dan kondisi kendaraan menjadi faktor utama terjadinya kecelakaan. Komposisi kendaraan ringan dan berat yang cukup seimbang turut meningkatkan peluang kecelakaan mengingat perbedaan kecepatan dan ukuran antara kedua jenis kendaraan. Beberapa rekomendasi yang dapat diterapkan untuk mengurangi kecelakaan antara lain penerapan alat manajemen insiden, pemasangan marka chevron, dan konstruksi escape ramp.